OXYTOCIN AND THE CARDIOVASCULAR SYSTEM: ANATOMICAL AND PHYSIOLOGICAL CONCEPTS (Multidisciplinary Journal of Science and Technology, 2025)
Oxytocin, a neuropeptide hormone primarily known for its roles in social bonding, childbirth, and lactation, has garnered increasing attention for its effects on cardiovascular physiology. It is synthesized in the hypothalamus and released from the posterior pituitary, exerting regulatory effects on the heart, blood vessels, and autonomic nervous system. Oxytocin interacts with the cardiovascular system by modulating vascular tone, blood pressure, and cardiac function through direct actions on oxytocin receptors (OXTR) in the endothelium, myocardium, and autonomic nervous structures. Additionally, it plays a role in stress-induced cardiovascular responses and has been implicated in protective mechanisms against hypertension, atherosclerosis, and ischemic heart disease. This review aims to provide a comprehensive analysis of the anatomical pathways, physiological mechanisms, and potential clinical implications of oxytocin in cardiovascular regulation.